CDC73-related hereditary hyperparathyroidism: five new mutations and the clinical spectrum - Frank-Raue, Karin; Haag, Christine; Schulze, Egbert; Keuser, Roger; Raue, Friedhelm; Dralle, Henning; Lorenz, Kerstin (European journal of endocrinology, 2011)
Hyperparathyroidism-jaw tumour (HPT-JT) syndrome is a rare autosomal dominant cause of benign and malignant parathyroid tumours, ossifying jaw tumours, various cystic and neoplastic renal abnormalities and benign and malignant uterine tumours. Disease-causing mutations have been localised in the tumour suppressor gene CDC73. There is limited information available on the mutations, and resulting phenotypes and long-term follow-up data are especially scarce.We analysed the clinical data from 16 patients (including three families) carrying mutations in the CDC73 gene. We describe five new mutations/gene variants, the corresponding phenotypes of these carriers and the long-term follow-up.The 16 patients were evaluated at an endocrine outpatient clinic and at a surgical department. DNA samples were obtained for sequence analysis of the CDC73 gene.Clinical features of HPT-JT syndrome were detected in 13 of the 15 carriers with germline CDC73 mutations. The major features were benign (n=7; 47%) or cancerous (n=3; 20%) HPT-JT was present in eight cases (53%). Most patients had severe hypercalcaemia, and median serum calcium levels were 3.36mmol/l. A patient with non-secretory parathyroid carcinoma was included. HPT was diagnosed at a median age of 28.5 years. Mutational analysis of the CDC73 gene identified eight sequence changes, three of them have been reported previously, whereas five are novel: c.1346delG, c.88_94delTTCTCCT, the non-coding variants, c.307+5G>T and c.424−5T>C and c.*12C>A of unknown significance.This study significantly increases the information available on the mutations and phenotypes of HPT-JT syndrome.